Advanced Real-Time Hierarchical Task Network: Long-Term Behavior in Real-Time Games - Namiki, Kousuke; Mori, Tomohiro; Miyake, Youichiro; Sakata, Shinpei; Martins, Gustavo (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2021)
HTN (Hierarchical Task Network) is a widespread technique in the game industry to achieve long-term behavior and smart intelligence in NPCs. However, in the more real-time games of recent years, a situation has emerged where the system is not functioning effectively. We understand the re-planning process is the fundamental problem of HTN in real-time games and propose a new method to solve this problem.